Marketing system, socio economic role and intra household dynamics of indigenous chicken in Gomma Wereda, Jimma Zone, Ethiopia - Meseret, M.; Solomon, D.; Tadelle, D. (2011)
A survey of marketing system, socio economic role and intra household dynamics of indigenous chicken was conducted in Gomma Wereda located at 390 km southwest of Addis Ababa. Six Kebeles of the Wereda were randomly identified and 30 households (hh) randomly selected from each kebele were used to collect data on the profile of the respondents, chicken population and flock structure, marketing system, socio economic role and intra household dynamics of the indigenous chicken using questionnaire, regular visit and target group discussions. The results obtained showed that the mean flock size/hh of the study area (6.23 chickens) was greater than that of the national average (4.1) and strangely dominated by hens of > 5 months of age. Informal and open markets of live birds and eggs are common throughout the Wereda. There is variation in market price of chickens and eggs attributed to the physical condition of the birds, disease outbreak, time of incubation, and holidays and festivals. Both eggs and chickens pass through different individuals before reaching consumers and about 52.2% of the market chickens and eggs are collected and transported by retailers to terminal markets contributing to disease spread and quality deterioration. About 96.7% of the ownership of chicken was held by women and with the exception of poultry house construction all the other activities including marketing are done by women indicating that village chickens are source of self-reliance for women. There are no taboos connected to consumption of poultry. And yet, chickens and eggs are not among staple food items in the Gomma Wereda. The results obtained also showed that lack of access to credit and high prevalence of disease conditions and predators are the major constraints to improve household poultry in the study area.